2011
DOI: 10.1017/s1368980011001637
|View full text |Cite
|
Sign up to set email alerts
|

Consumer food choices: the role of price and pricing strategies

Abstract: Objective: To study differences in the role of price and value in food choice between low-income and higher-income consumers and to study the perception of consumers about pricing strategies that are of relevance during grocery shopping. Design: A cross-sectional study was conducted using structured, written questionnaires. Food choice motives as well as price perceptions and opinion on pricing strategies were measured. Setting: The study was carried out in point-of-purchase settings, i.e. supermarkets, fast-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 30 publications
(41 reference statements)
8
127
0
5
Order By: Relevance
“…20 Food selection is also impacted by sociodemographic variables, as low-income consumers are more price-sensitive than high-income consumers. 21 The limitations of this study are similar to those of other nonfield experiments. The study sample was a convenience sample of adults from an online panel.…”
Section: Consumer Perceptions Of Front-of-package Labellingsupporting
confidence: 52%
See 1 more Smart Citation
“…20 Food selection is also impacted by sociodemographic variables, as low-income consumers are more price-sensitive than high-income consumers. 21 The limitations of this study are similar to those of other nonfield experiments. The study sample was a convenience sample of adults from an online panel.…”
Section: Consumer Perceptions Of Front-of-package Labellingsupporting
confidence: 52%
“…Standard attributes used in market research on product labelling were used in the survey. The surveys were conducted in English and French and took place August [16][17][18][19][20][21]2011. The results were weighted by age, region and gender according to Statistics Canada 2006 Census data.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the majority of subjects immediately started to consider energy content or other ingredients to be the key factors in food selection, as also observed by Visschers et al (23) . Our study's findings regarding food choice criteria (Table 2) are consistent with reports from previous studies which emphasized the importance of familiarity with the product (7,30) and especially the product's taste and price (10,12) . Also, Grunert et al (8) have similarly reported that the most important food selection criterion was taste (52 % of answers), followed by 'this is what my family wants' (4) Ham (13), chicken/turkey (20), beef (2), mixed ingredients (1) 12 chose fatty products, such as salami in T*, but no one chose fatty products in W-, the leanest thin cold cuts were selected by 9 in T* and by 20 in WReady meal…”
Section: Discussionsupporting
confidence: 91%
“…Several studies emphasize that cost is one of the most important determinants of consumer food choice (44,45) . Therefore, household income may be a more appropriate measure of the SES of the household.…”
Section: Discussionmentioning
confidence: 99%